Assessing the Integration of Sustainable Development Goals in Higher Education: Evidence from a Quantitative Survey of Institutional Practices - Schneider, Lucas (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2012)
Higher education institutions are increasingly expected to contribute to the achievement of the Sustainable Development Goals (SDGs) through teaching, research, and community engagement. Despite growing awareness of sustainability within academic institutions, the extent to which SDGs are systematically integrated into higher education remains uncertain. This study investigates the level of SDG integration within universities and identifies key factors influencing its implementation using a quantitative survey approach. Data were collected from 200 respondents, including educators, students, and administrators from multiple higher education institutions. The survey instrument measured perceptions of institutional commitment, curriculum integration, digital infrastructure, and stakeholder engagement in sustainability initiatives. The results indicate that while universities demonstrate moderate levels of institutional commitment to sustainability, the integration of SDGs into curricula remains limited. Statistical analysis further reveals that institutional support and digital learning infrastructure significantly influence the effectiveness of SDG implementation. Additionally, stakeholder awareness, particularly among students, plays an important role in promoting sustainability initiatives within universities. The study highlights the need for comprehensive institutional strategies that combine policy commitment, technological readiness, and active stakeholder participation to enhance the role of higher education in achieving global sustainability goals.